A novel model of artificial intelligence based automated image analysis of CT urography to identify bladder cancer in patients investigated for macroscopic hematuria - Suleiman Abuhasanein; Lars Edenbrandt; Olof Enqvist; Staffan Jahnson; Henrik Leonhardt; Elin Trägårdh; Johannes Ulén; Henrik Kjölhede (Scandinavian Journal of Urology)
Objective: To evaluate whether artificial intelligence (AI) based automatic image analysis utilising convolutional neural networks (CNNs) can be used to evaluate computed tomography urography (CTU) for the presence of urinary bladder cancer (UBC) in patients with macroscopic hematuria.